Involving Audio-lingual Method (ALM) and Communicative Language Teaching (CLT) in Teaching Speaking Skill at Junior High School - Siska Aris Nita; An Fauzia R. Syafei (Universitas Negeri Padang, 2012)
This article explain about teaching speaking skill by using Audio-lingual Method (ALM) and Communicative Language Teaching (CLT). In classroom activities, ALM is the first method. The teacher drills the students’ pronunciation by using some drills in ALM techniques. After the students understand how to pronouns it, the teacher use CLT as the continuation method. In CLT, the teacher gives a picture and the situation to the students and asks the students to make a short conversation based on the situation in the picture. In this activities, the teacher use role play as the classroom activities. AbstrakArtikel ini menguraikan tentang pengajaran speaking skill dengan menggunakan metode Audio-lingual Method (ALM) dan Communicative Language Teaching (CLT). Dalam aktivitas pengajarannya, ALM adalah metode pertama yang digunakan. Guru melatih pengucapan (pronunciation) siswa dengan menggunakan drill-drill yang ada pada ALM. Setelah siswa paham bagaimana cara pengucapannya (pronunciation), guru menggunakan CLT sebagai metode lanjutan dari ALM. Dalam CLT, guru memberikan sebuah gambar dan situasinya kepada siswa dan menyuruh siswa membuat sebuah percakapan pendek berdasarkan situasi yang ada di dalam gambar tersebut. Dalam aktivitas ini, guru menggunakan role play sebagai aktivitas di dalam kelas. Kata kunci: Transactional and interpersonal text, Audio-lingual Method, Repetation, Communicative Language Teaching, Role play